SINTESA KATALIS SUPER ASAM SO42-/ ZnO UNTUK PRODUKSI BIODIESEL DARI MINYAK KELAPA SAWIT - Inshani Utami; Roikhatus Solikhah; I. Istadi (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
The issue of energy is a global issue that must be discussed by all countries in the world. Rising oil prices and a dwindling supply push every country to develop new renewable energy alternatives. One of this alternative energy is biodiesel. The biodiesel production can be done by using vegetable oil as the raw material over supported homogeneous catalyst, heterogeneous catalyst and enzymatic catalyst. In this study the use of palm oil as the main material to be reacted with methanol and the catalyst used as heterogeneous catalysts SO42-/ZnO by changing variables used are long reaction times (1, 2.5 and 4 hours) and the weight ratio of catalyst / oil (4 , 6, and 8).The studybeganwith thepreparation of catalyst SO42-/ZnO followed by aransesterification reaction between palm oil with methanol. The resultsofthis studyshowed that the super acid catalyst SO42-/ZnOcan be usedin making biodiesel.Optimum operatingcondition for this catalytic reaction is the weight ratio of catalyst/oil 3,8 during 2,5 hours with 78%  yield of the resulting ester metal.Longer time ofthe transesterificationreaction, the higher the % yield ofthe resulting ester metal, while adding more catalyst produced the lower theyield.